Measuring inclusive wealth of China: Advances in sustainable use of resources. (15th June 2020) - Jingyu, Wang; Yuping, Bai; Yihzong, Wurihan; Zhihui, Li; Xiangzheng, Deng; Islam, Moinul; Managi, Shunsuke
Abstract: The inclusive wealth approach is increasingly common to measure the sustainable development of the countries. It comprised the natural, human and produced capital of nations to measure social wellbeing. We measure the inclusive wealth of the provinces in China from 2000 to 2015 and reports the sustainable use of the resources. We identify that three types of capital have increased to varying degrees, with produced capital increasing by 615.6%, natural capital increasing by 33.8%, and human capital increased by 337.0%. The total amount of inclusive wealth has increased by 300.4% in the past 15 years. However, the provinces in China are still facing unbalanced development across the country compared to developed nations. The use of the natural capital, more specifically now-renewable resources, has been restricting the wealth growth in some provinces. Although ecological services account for a small proportion of the total inclusive wealth, more attention is essential for sustainable development. Meanwhile, the rapid growth of carbon damages posed threat to future wealth accumulation. Innovative, coordinated, green, open and shared development are the goals of China 13th and 14th five-year plan and our inclusive wealth of China will be key measurement tool of this achievement. Highlights: This study focus on inclusive growth of the provinces in China. On average, inclusive wealth growth is 300.4% from 2000 to 2015 in China. Produced, natural and human capital growth is 615.6%, 33.8% and 337% respectively. Reduction of the use of non-renewable natural resources slow down the growth in some provinces. Carbon damages posed threat to the future wealth accumulation in China.